Transporte em um sistema binário de partículas autopropelidas - Oliveira, Jessé Pereira de (2015)
Originally introduced by T. Vicksek et al. [Phys. Rev. Lett. 75, 1226 (1995)], Self Propelled Particles (SPP) have an intrinsic constant speed which suffer variations ins its direction as results of external perturbations (another particles or system) and are used to model systems that shows agglomeration effects. The concept of SPP is applied to describe and understand dynamic effects of agglomeration in natural systems, such as living micro-organisms (bacteria, virus, etc.) and colonies of individuals which move in flocks (fishes, sheep, bees) or, artificially produced, as colloidal systems especially prepared in laboratory. The study of SPP has its relevance in several areas of knowledge, such as material engineering, medicine and sciences of nature (physics, chemistry and biology). In most of cases, the collective motion has an well-differentiated behaviour of the individual motion of the components of a given system. So, the movement of a certain individual is affected by the presence of the other elements of the system, changing its general behaviour, as direct consequences of the direct interaction between them. In this way, we see the importance of investigation and understanding of collective motion of the SPP. Especially in this dissertation, we study a binary two-dimensional system of SPP subject to the presence of rigid obstacles with anisotropic geometry (semi-circles) distributed neatly in form of a square web. Beyond the particle-particle and particleobstacle interaction, the individual movement of each SPP suffers influence of an white noise. The objective is characterize the transport of SPP trough the two-dimensional substratum in absence of an propeller external force. We present and systematic study of collective motion of SPP in function of the speed of the particles, of the noise intensity which defines the stochastic movement of SPP, of the size of the obstacles, of the SPP density e the separation between the obstacles. Due the anisotropy of the obstacles, arise an spontaneous and ordered collective motion in normal direction of the plane surface of the obstacles, characterized by an non-null mean speed for each type of SPP in absence of an external force which in affected by the system parameters.